Gender, Protection Orders, and Intimate Partner Violence in Later Life: A Study of Protective Order Filings in Arizona - Durfee, Alesha (Journal of interpersonal violence, 2021)
Most analyses of domestic violence and older adults focus on abuse by children and non-intimate caregivers. However, a significant percentage of elder abuse is perpetrated by an intimate partner. This article addresses a gap in the current literature on elder abuse by addressing how older survivors of intimate partner violence use the legal system as a tool to achieve safety by filing for a civil protection order. We critically examine 607 Arizona protection order filings in 2015, comparing those petitions filed by adults 50 and older (n = 83) with those younger than 50 (n = 524). We find significant differences in the forms of violence described in the protection order petition, as well as the types of relationships between the petitioner and respondent, the likelihood that an order will be issued, and the provisions requested and granted. Most importantly, gender is a critical component of our analysis—older petitioners are far more likely to be men than younger petitioners, and both petitions and outcomes are very different for older men than for older women. These results are then discussed in the context of the dynamics of older relationships, current firearm laws, and the barriers older adults face when attempting to use resources intended to help survivors achieve safety.